Clinical significance of transient left ventricular dilation assessed during myocardial Tc-99m sestamibi scintigraphy - Duarte,Paulo Schiavom (2003)
OBJECTIVE: To assess the clinical significance of transient ischemic dilation of the left ventricle during myocardial perfusion scintigraphy with stress/rest sestamibi. METHODS: The study retrospectively analyzed 378 patients who underwent myocardial perfusion scintigraphy with stress/rest sestamibi, 340 of whom had a low probability of having ischemia and 38 had significant transient defects. Transient ischemic dilation was automatically calculated using Autoquant software. Sensitivity, specificity, and the positive and negative predictive values were established for each value of transient ischemic dilation. RESULTS: The values of transient ischemic dilation for the groups of low probability and significant transient defects were, respectively, 1.01 ± 0.13 and 1.18 ± 0.17. The values of transient ischemic dilation for the group with significant transient defects were significantly greater than those obtained for the group with a low probability (P<0.001). The greatest positive predictive values, around 50%, were obtained for the values of transient ischemic dilation above 1.25. CONCLUSION: The results suggest that transient ischemic dilation assessed using the stress/rest sestamibi protocol may be useful to separate patients with extensive myocardial ischemia from those without ischemia.